2018
DOI: 10.1088/1748-0221/13/10/c10002
|View full text |Cite
|
Sign up to set email alerts
|

Study of electromigration phenomena in Au/p-type CdTe with two Schottky contacts

Abstract: In this work we present the transient measurements along a Au/CdTe/Au structure in the temperature range of 323K-363K to deepen the understanding of the electromigration phenomena. Removal of the anode contact and of a thin layer below was necessary after each measurement to have similar distribution of the donor ions in the depletion region for each new measurement. The diffusion coefficients at different temperatures have been determined and the activation energy of the electromigration process was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Kim et al [ 17 ] showed the improvement in the mobility-lifetime product after the treatment of CZT at 493 K at a voltage of 60 V for 7 and 60 days, which they assigned to the electromigration of Cu, Fe, and Ga impurities. Additional studies demonstrated the electromigration of positively charged donors in CdTe-based materials, which mainly affect the electrical properties [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [ 17 ] showed the improvement in the mobility-lifetime product after the treatment of CZT at 493 K at a voltage of 60 V for 7 and 60 days, which they assigned to the electromigration of Cu, Fe, and Ga impurities. Additional studies demonstrated the electromigration of positively charged donors in CdTe-based materials, which mainly affect the electrical properties [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%